Characterization of AlGaN/GaN HEMTs with Different Manufacturing Characteristics - Panzo, E. C. [UNESP]; Candido, J. [UNESP]; Junior, N. Graziano [UNESP]; Simoen, E.; Andrade, M. G.C. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
This work presents the characterization of high mobility transistors (AlGaN/GaN HEMTs) produced with different techniques in the manufacturing process. The study performs a comparative analysis of the respective HEMTs. Here it is demonstrated that efficient HEMTs can be developed using 2 active implants without the need for specific heat treatment processes to create ohmic contacts or activate the device. The devices thus produced had higher drain current (Id), output conductance (gd), transconductance (gm), field effect mobility (μeff), effective mobility (μFE) and low field mobility (μ0), in addition to lowest series resistance (RSD), threshold voltage (VT) and subthreshold slope (S). These results indicate that the adopted methodology not only simplifies the manufacturing process but also significantly improves the performance of HEMTs. Keywords - HEMT, Manufacturing process, Gate metal, Series resistance, Ohmic contacts, GaN channel.